Chitosan-quaternary ammonium salt modified composite shale inhibitor and preparation method thereof

The shale inhibitor prepared by combining modified chitosan with quaternary ammonium salt solves the problems of insufficient green environmental protection and thermal stability of existing drilling fluid inhibitors, and achieves effective inhibition of shale formations and wellbore stability, making it suitable for drilling in complex formations.

CN120988658APending Publication Date: 2025-11-21SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511153272.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing drilling fluid inhibitors are insufficient in terms of environmental friendliness, thermal stability, and inhibitory effect, making it difficult to meet the wellbore stability requirements of shale formations.

Method used

Using chitosan as a carrier, a composite shale inhibitor was prepared by grafting quaternary ammonium salt monomer DMDAAC onto the shale and adding small molecule glycine as a synergist. The inhibitor works synergistically on the shale clay structure through mechanisms such as ion exchange, electrostatic adsorption and surface coating.

Benefits of technology

It significantly improves the ability of water-based drilling fluids to suppress clay minerals, has good thermal stability and environmental friendliness, is suitable for high-temperature and high-pressure formations, and meets the drilling requirements of deep wells and shale gas wells.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of petroleum drilling engineering, and discloses a chitosan-quaternary ammonium salt modified composite shale inhibitor and a preparation method thereof. According to the inhibitor, natural chitosan is used as a main chain, dimethyl diallyl ammonium chloride (DMDAAC) is adopted for free radical grafting modification, glycine is combined as a synergistic auxiliary agent, and a composite structure with high cation density is constructed. The preparation method comprises the following steps: dissolving 15-25 parts of chitosan in 1000 parts of 1% glacial acetic acid, and stirring at room temperature; dropwise adding 2 to 4 parts of DMDAAC, reacting at 65 to 75 DEG C, and then adding 0.1 to 1 part of ammonium persulfate for grafting for 3.5 to 4.5 hours; and cooling, filtering and drying to obtain powder. And dissolving 10-20 parts of the solution in deionized water, adding 1.5-2.5 parts of glycine, and uniformly mixing to obtain the composite inhibition liquid. The inhibitor has good water solubility and thermal stability, can significantly inhibit shale hydration expansion and particle dispersion, and experiments show that the inhibitor can be suitable for well wall stability control of complex stratums such as high-temperature deep wells and the like, and has good field adaptability and industrial popularization value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention discloses a chitosan-quaternary ammonium salt composite shale inhibitor and its preparation method, belonging to the field of petroleum drilling engineering technology. Specifically, it relates to an environmentally friendly shale inhibitor material obtained by grafting and modifying natural high molecular weight chitosan with quaternary ammonium salt monomers. Background Technology

[0002] Shale formations, a type of sedimentary rock widely distributed in terrestrial and marine sedimentary environments, play a crucial role in oil and gas resource exploration and development. However, shale formations often exhibit poor wellbore stability during drilling, which has become a key factor in a series of complex accidents such as wellbore collapse, wellbore enlargement, and stuck pipe. This is because shale contains a large amount of water-sensitive clay minerals, especially montmorillonite, illite, and kaolinite. These minerals have significant hydrophilicity and a layered structure, making them prone to hydration, expansion, stripping, and dispersion upon contact with water-based drilling fluids, thereby causing formation structural damage and leading to wellbore instability.

[0003] During drilling, inhibitors are typically added to the drilling fluid system to improve its shale suppression performance and slow down the hydration and expansion process. Currently, widely used inhibitors mainly include inorganic salts (such as potassium chloride and sodium chloride), organic cationic polymers (such as quaternary ammonium salts), high-molecular-weight polycations, and nanoparticles. These inhibitors reduce the contact between shale and water through different mechanisms of action, such as ion exchange, electrostatic neutralization, surface adsorption, and physical shielding, thereby improving wellbore stability.

[0004] Potassium chloride (KCl) is widely used in water-based drilling fluid systems due to its good inhibitory effect and ease of use. KCl reduces the swelling properties of shale by exchanging potassium ions with exchangeable cations in shale; however, its high concentration (generally 3%–10%) causes significant environmental pollution to surface water and soil after discharge, posing a potential threat, especially to agricultural ecosystems. Furthermore, KCl has limited inhibitory effects on high-temperature, high-pressure shale formations, posing a risk of failure.

[0005] To overcome the environmental pollution and insufficient thermal stability of KCl, researchers have developed various quaternary ammonium salts and polycationic inhibitors, such as DMDAAC (dimethyl diallyl ammonium chloride) and PDMDAAC (polydimethyl diallyl ammonium chloride). These inhibitors possess strong cationic properties, forming an adsorption film on the shale surface and neutralizing negative charges, effectively preventing shale flake stripping and dispersion. However, due to their complex synthesis routes, high costs, and the fact that most are petroleum-based monomers that are difficult to degrade, they still face environmental sustainability issues. Furthermore, they are prone to adsorption saturation or structural degradation during long-term drilling cycles, leading to a decrease in inhibitory efficacy.

[0006] In recent years, green and environmentally friendly inhibitors have become a research hotspot. An ideal inhibitor should possess the following characteristics: good thermal stability, strong inhibitory effect, no corrosion to shale, stable dispersion in aqueous solution, non-toxic and harmless to the environment, low cost, and sustainable availability. Drilling fluid inhibitors based on modified natural polymer materials, especially chitosan, lignin, and starch, have become an important direction in novel inhibitor research due to their degradability, non-toxicity, and tunable structure. Among them, chitosan molecules contain a large number of amino and hydroxyl functional groups, exhibiting good adsorption capacity, biodegradability, and modification flexibility, making it a preferred carrier for preparing green inhibitors.

[0007] In summary, while existing inhibitors have shown some effectiveness in suppressing shale hydration in the short term, they still have many shortcomings in terms of environmental friendliness, thermal stability, cost control, and long-term performance. Therefore, developing a novel shale inhibitor based on natural polymer materials, with simple modification, excellent inhibitory effect, good thermal stability, and environmental friendliness, has significant engineering application value and research significance for ensuring drilling safety and promoting the development of green petroleum engineering. Summary of the Invention

[0008] This invention provides a chitosan-quaternary ammonium salt modified composite shale inhibitor and its preparation method, aiming to solve the technical bottlenecks of existing drilling fluid inhibitors in terms of environmental friendliness, thermal stability, and inhibitory effect. To address these issues, this invention uses natural polysaccharide chitosan as a carrier, performs cationic modification by grafting quaternary ammonium salt monomers (DMDAAC), and combines it with small-molecule glycine as a synergistic agent to prepare a green, biodegradable composite shale inhibitor with strong inhibitory capabilities. This inhibitor can synergistically act on the shale clay structure through multiple mechanisms such as ion exchange, electrostatic adsorption, and surface coating, significantly inhibiting hydration swelling and dispersion. Experimental results show that this inhibitor exhibits excellent inhibitory performance and thermal stability at both room temperature and 150℃, and has good dispersibility in water, is environmentally friendly, and is suitable for water-based drilling fluid systems in complex formation conditions such as shale gas wells, deep wells, and high-temperature, high-pressure wells, showing broad industrial application prospects.

[0009] To prepare this complex inhibitor, the first aspect of the present invention provides a preparation method. The method includes: (1) Weigh 15-25 parts by weight of chitosan powder (degree of deacetylation 80%-90%, molecular weight 100,000-200,000), slowly add it to 1,000 parts of 1% glacial acetic acid aqueous solution, and stir continuously at room temperature (25°C) for 1.2-2.5 hours to form a uniform solution. (2) Under stirring, slowly add 2 to 4 parts of dimethyl diallyl ammonium chloride (DMDAAC) to the above chitosan solution. During the addition process, keep the system temperature between 65 and 75°C. After the addition is completed, continue stirring for 25 to 35 minutes to ensure that the monomer is evenly dispersed. (3) Dissolve 0.1 to 1 part ammonium persulfate (APS) as a free radical initiator in 10 parts distilled water, and slowly add it dropwise to the reaction system. Maintain the reaction temperature at 65 to 75°C for 3.5 to 4.5 hours to carry out the graft copolymerization reaction; (4) After the reaction is completed, the mixture is allowed to cool naturally to room temperature, filtered to remove unreacted impurities, and dried to obtain a light yellow modified chitosan inhibitor solid powder. (5) Add 10-20 parts of the obtained inhibitor powder to 1000 parts of deionized water, and stir magnetically for 25-30 minutes at room temperature until completely dissolved to form a uniform inhibitory solution. Then add 1.5-2.5 parts of glycine as a synergistic agent and continue stirring until uniform to finally obtain a composite shale inhibitory solution. A second aspect of the present invention provides a chitosan-quaternary ammonium salt composite shale inhibitor prepared by the method described in the first aspect, the characteristics of which include: (1) Using chitosan as the main chain structure, cationic quaternary ammonium salt groups are introduced through chemical modification to construct a green natural polymer backbone with high cationic density. (2) Introducing small molecule glycine as a synergistic inhibitor enhances the adsorption and plugging ability of drilling fluid on shale surface, achieving a dual chemical-physical effect; (3) It is synthesized by free radical-initiated polymerization, which is mild and the process is controllable. The product is a water-soluble solid powder, which is convenient for transportation and on-site addition. (4) It has good water solubility and dispersibility, and can be synergistically formulated with conventional drilling fluid treatment agents without affecting other performance indicators of drilling fluid; (5) It has obvious thermal stability and shear resistance, and is suitable for high temperature and high pressure formations, meeting the drilling requirements of harsh working conditions such as deep wells and shale gas wells; (6) It is green, environmentally friendly and biodegradable, which helps to improve the ecological safety level of drilling fluid and is in line with the development trend of green and low-carbon oil and gas development technology.

[0010] Through the above technical solution, the present invention can achieve the following excellent effects: (1) The chitosan-quaternary ammonium salt composite shale inhibitor provided by this invention can significantly improve the inhibition ability of water-based drilling fluids on clay minerals and effectively control the hydration swelling and dispersion behavior of shale wellbore. Experiments show that the inhibitor of this invention can reduce the free swelling rate of bentonite to below 50% at low concentrations (1.5%~2.0%), and after hot rolling at 120℃ and 150℃ for 16 hours, it still maintains a good inhibition effect with a swelling rate not exceeding 65%. This inhibitor has good dispersibility and strong compatibility in water, can be directly used in conventional water-based drilling fluid systems, and has no significant adverse effects on rheology and rock-carrying capacity.

[0011] (2) This inhibitor is based on natural chitosan, which has good biodegradability and environmental friendliness, and significantly reduces the environmental pollution risk caused by traditional inorganic salt and organic amine inhibitors. The density of cationic groups in its structure can be adjusted, which can achieve efficient interaction with formation clay minerals and meet the wellbore stability requirements under complex geological conditions such as deep wells and high-temperature wells.

[0012] In summary, this invention achieves comprehensive technical effects of strong inhibition, high thermal stability, environmental friendliness, and wide applicability, and has good industrial promotion value and engineering application prospects. Detailed Implementation

[0013] The ranges and material values ​​described in this invention are not precisely within the exact range. All ranges and values ​​described in this invention are included within these ranges or values. For these given numerical ranges, ranges and their endpoints can be combined to form a new numerical range. These combined new values ​​should also be considered as the content disclosed in this invention.

[0014] Note that the following detailed description of specific embodiments of the present invention is for illustrative and explanatory purposes only and does not limit the scope of the invention.

[0015] The first aspect of this invention provides a preparation method, the method comprising: (1) Weigh 10-30 parts of modified chitosan by weight and dissolve it in 1000 parts of 1% glacial acetic acid. Stir at room temperature for 1.5-2.5 hours to form a homogeneous solution. (2) Add 2 to 4 parts of dimethyl diallyl ammonium chloride (DMDAAC) to the chitosan solution prepared in step (1) and heat to 70°C; (3) Slowly add 0.1~1 part of ammonium sulfate to the solution after the reaction in step (2) and carry out the graft copolymerization reaction at a temperature of 65~75℃ for 4.5~5.5 hours; (4) After the reaction is completed, the mixture is naturally cooled to room temperature, unreacted impurities are removed by filtration, and then freeze-dried to obtain a light yellow modified chitosan inhibitor solid powder. (5) Add 10-20 parts of the prepared inhibitor to 1000 parts of water, stir evenly, then add 1.5-2 parts of glycine as a blocking agent, mix evenly, and obtain a composite inhibitory solution.

[0016] The present invention will be described in detail below through examples. Unless otherwise specified, all other materials used in the embodiments and comparative examples of the present invention are common commercially available products.

[0017] Preparation Example 1: 15 parts of chitosan were weighed and dissolved in 1000 parts of 1% glacial acetic acid. The solution was stirred at room temperature for 2 hours to form a homogeneous solution. Then, 2 parts of dimethyl diallyl ammonium chloride (DMDAAC) were slowly added dropwise to the solution and heated to 70°C. The solution was stirred evenly under constant temperature conditions. Subsequently, 0.5 parts of ammonium persulfate were added as an initiator, and the temperature was controlled at 70°C to carry out a free radical initiated copolymerization reaction for 5 hours to form a modified chitosan cationic polymer. After the reaction was completed, the solution was naturally cooled to room temperature, filtered to remove unreacted impurities, and then freeze-dried at -40°C and then vacuum-dried at 50°C for 18 hours to obtain a light yellow modified chitosan inhibitor solid powder. The inhibitor was added to 1000 parts of distilled water at a ratio of 15 parts, stirred evenly, and then 1.5 parts of glycine were added and mixed evenly to obtain a composite inhibitor solution, denoted as S1.

[0018] Preparation Example 2: 20 parts of chitosan were weighed and dissolved in 1000 parts of 1% glacial acetic acid. The solution was stirred at room temperature for 2 hours to form a homogeneous solution. Then, 3 parts of dimethyl diallyl ammonium chloride (DMDAAC) were slowly added dropwise to the solution and heated to 70°C. The solution was stirred evenly under constant temperature conditions. Subsequently, 0.5 parts of ammonium persulfate were added as an initiator, and the temperature was controlled at 70°C for a free radical-initiated copolymerization reaction for 5 hours to form a modified chitosan cationic polymer. After the reaction was completed, the solution was naturally cooled to room temperature, filtered to remove unreacted impurities, and then freeze-dried at -40°C and then vacuum-dried at 50°C for 18 hours to obtain a light yellow modified chitosan inhibitor solid powder. The inhibitor was added to 1000 parts of distilled water at a ratio of 15 parts, stirred thoroughly, and then 2 parts of glycine were added and mixed evenly to obtain a composite inhibitor solution, denoted as S2.

[0019] Preparation Example 3: 25 parts of chitosan were weighed and dissolved in 1000 parts of 1% glacial acetic acid. The solution was stirred at room temperature for 2 hours to form a homogeneous solution. Then, 4 parts of dimethyl diallyl ammonium chloride (DMDAAC) were slowly added dropwise to the solution and heated to 70°C. The solution was stirred evenly under constant temperature conditions. Subsequently, 0.5 parts of ammonium persulfate were added as an initiator, and the temperature was controlled at 70°C to carry out a free radical initiated copolymerization reaction for 5 hours to form a modified chitosan cationic polymer. After the reaction was completed, the solution was naturally cooled to room temperature, filtered to remove unreacted impurities, and then freeze-dried at -40°C and then vacuum-dried at 50°C for 18 hours to obtain a light yellow modified chitosan inhibitor solid powder. The inhibitor was added to 1000 parts of distilled water at a ratio of 15 parts, stirred evenly, and then 2.5 parts of glycine were added and mixed evenly to obtain a composite inhibitor solution, denoted as S3.

[0020] Comparative Example 1: 10 parts of chitosan were dissolved in 1000 parts of 1% glacial acetic acid and stirred at room temperature for 2 hours to form a homogeneous solution. Then, 1.5 parts of dimethyl diallyl ammonium chloride (DMDAAC) were slowly added dropwise to the above solution and heated to 70°C, and stirred evenly under constant temperature conditions. Subsequently, 0.1 parts of ammonium persulfate were added as an initiator, and the temperature was controlled at 70°C to carry out a free radical initiated copolymerization reaction for 5 hours to form a modified chitosan cationic polymer. After the reaction was completed, the mixture was naturally cooled to room temperature, filtered to remove unreacted impurities, and then freeze-dried at -40°C and then vacuum-dried at 50°C for 18 hours to obtain a light yellow modified chitosan inhibitor solid powder. The above inhibitor was added to 1000 parts of distilled water at a ratio of 15 parts, stirred thoroughly, and then 1 part of glycine was added and mixed evenly to obtain a composite inhibitor solution, denoted as S4.

[0021] Comparative Example 2: 30 parts of chitosan were dissolved in 1000 parts of 1% glacial acetic acid and stirred at room temperature for 2 hours to form a homogeneous solution. Then, 5 parts of dimethyl diallyl ammonium chloride (DMDAAC) were slowly added dropwise to the above solution and heated to 70°C, and stirred evenly under constant temperature conditions. Subsequently, 1 part of ammonium persulfate was added as an initiator, and the temperature was controlled at 70°C to carry out a free radical initiated copolymerization reaction for 5 hours to form a modified chitosan cationic polymer. After the reaction was completed, the mixture was naturally cooled to room temperature, filtered to remove unreacted impurities, and then freeze-dried at -40°C and then vacuum-dried at 50°C for 18 hours to obtain a light yellow modified chitosan inhibitor solid powder. The above inhibitor was added to 1000 parts of distilled water at a ratio of 15 parts, stirred thoroughly, and then 3 parts of glycine were added and mixed evenly to obtain a composite inhibitor solution, denoted as S5.

[0022] Comparative Example 3: Weigh 50 parts of potassium chloride (KCl) and add it to 1000 parts of distilled water. Stir for 30 minutes at room temperature until completely dissolved to obtain a 5% potassium chloride solution; denoted as S6.

[0023] Comparative Example 4: Weigh 100 parts of potassium chloride (KCl) and add it to 1000 parts of distilled water. Stir at room temperature for 30 minutes until completely dissolved to obtain a 10% potassium chloride solution; denoted as S7.

[0024] Comparative Example 5: Weigh 15 parts of unmodified chitosan and add it directly to 1000 parts of distilled water. Dissolve it in 1% acetic acid aqueous solution and stir to form a homogeneous solution; denoted as S8.

[0025] To verify the inhibitory performance and anti-dispersion ability of the inhibitor described in this invention under both room temperature and high temperature conditions, the following tests were designed to compare the inhibitor of this invention with commonly used inhibitors. The tests were conducted in accordance with GB / T 29170-2012 "Experiments and Tests of Drilling Fluids for Petroleum and Natural Gas Industry". Test 1 used the bentonite free expansion test method. 2g of bentonite sample was added to each group of experimental liquids (100mL), and after standing for 24 hours, the expansion height was measured, and the expansion rate was calculated. Test 2 was a hot rolling experiment, using an API standard high-temperature roller furnace. After rolling at a set temperature (120℃ and 150℃) for 16 hours, the expansion rate was measured again. Test 3 determined the dispersion performance using the centrifugal sedimentation method. After centrifuging the hot-rolled sample, the suspended particle ratio in the supernatant was recorded, reflecting the system's anti-dispersion ability.

[0026] Test 1: Free Expansion Rate Analysis (Room Temperature) The experiment used standard shale bentonite samples, with an initial settling height of 8.0 mm. During the experiment, 2 g of shale bentonite sample was added to each group of experimental liquids (100 mL per group), and labeled S1, S2, S3, S4, S5, S6, S7, and S8 respectively. After each group of samples was left to stand in the corresponding composite inhibition solution for 12 hours, the height of the swelling layer was measured, and then the free swelling rate was calculated.

[0027] The initial settlement height was 8 mm. After standing for 12 hours, the height of the expansion layer was measured, and the free expansion rate was calculated. The test results after free expansion were as follows: S1 (12.4 mm), S2 (11.4 mm), S3 (11.2 mm), S4 (14.4 mm), S5 (11.8 mm), S6 (15.6 mm), S7 (15.5 mm), and S8 (13.8 mm). Their free expansion rates were S1 (55%), S2 (42.5%), S3 (40%), S4 (80%), S5 (47.5%), S6 (95%), S7 (87.5%), and S8 (72.5%), respectively.

[0028] Overall, experimental groups S2 and S3 exhibited superior swelling inhibition performance, with swelling rates of 42.5% and 40.0%, respectively. Their post-swelling heights were only 11.4 mm and 11.2 mm, significantly lower than the KCl control groups S6 (95.0%) and S7 (87.5%), and the unmodified chitosan group S8 (72.5%). These results indicate that the composite polymer material formed by grafting an appropriate amount of chitosan with quaternary ammonium salt (DMDAAC) can form an effective coating layer on the surface of shale particles, thereby significantly inhibiting the adsorption of water by bentonite and interlayer swelling.

[0029] Among them, group S4 had a low proportion of modified components, resulting in poor inhibition effect, and the expansion rate still reached 80.0%. Although group S5 had the highest addition ratio (30 parts chitosan and 5 parts DMDAAC), its free expansion rate was 47.5%, which was slightly lower than that of S2 and S3. This may be because the high concentration of polymers led to an increase in the viscosity of the solution system and a decrease in diffusivity, thus affecting the uniformity of its adsorption on the particle surface.

[0030] In summary, using appropriate proportions of composite modification (such as S2 and S3 groups) to maintain the inhibitory effect while taking into account solution permeability is a better strategy for suppressing shale hydration swelling.

[0031] Test 2: Thermal Expansion Rate Analysis (120°C & 150°C) To further investigate the inhibitory performance and thermal stability of the prepared inhibitor in a high-temperature downhole environment, a hot rolling expansion experiment was conducted at 150℃. After the samples were hot rolled for 16 hours, the swelling height of the bentonite was measured and the hot rolling expansion rate was calculated.

[0032] The initial height was 8 mm, and the heights after thermal expansion were S1 (13.1 mm), S2 (12 mm), S3 (11.9 mm), S4 (15.6 mm), S5 (12.2 mm), S6 (18.0 mm), S7 (16.8 mm), and S8 (15.2 mm), respectively. Their thermal expansion rates were S1 (63.8%), S2 (50.0%), S3 (48.8%), S4 (95.0%), S5 (52.5%), S6 (125.0%), S7 (110.0%), and S8 (90.0%), respectively.

[0033] Experimental results showed that group S3 maintained the best performance, with an expansion height of 11.9 mm after hot rolling, corresponding to an expansion rate of 48.8%. Group S2 followed closely behind (50.0%), demonstrating stable inhibitory performance even under long-term high-temperature conditions. In contrast, the expansion rates of the KCl control groups S6 and S7 increased sharply to 125.0% and 110.0% respectively at high temperatures, indicating that the ion exchange effect of traditional ionic inhibitors weakens under high-temperature conditions, resulting in a significant decrease in inhibitory ability.

[0034] In addition, the expansion rate of group S4 after hot rolling is as high as 95.0%, which is basically the same as its free expansion rate, indicating that it lacks an effective high-temperature suppression structure; group S5 still maintains good thermal stability (52.5%), but is slightly inferior to S3, further confirming the rule that "excessive dosage does not necessarily bring better performance".

[0035] In summary, this study shows that the inhibitor obtained by modifying chitosan and quaternary ammonium salt in an appropriate ratio exhibits excellent performance under both free expansion and high-temperature thermal expansion conditions, and has good downhole applicability and thermal stability, which can meet the needs of high-temperature drilling operations in shale formations.

[0036] Test 3: Dispersion Performance Analysis (Centrifugal Suspension Rate) Take 50 mL of each group of slurry samples after heat treatment, place them in standard centrifuge tubes, and centrifuge at 3500 rpm for 30 minutes. Record the volume and turbidity of the supernatant after centrifugation. Then, filter, dry, and weigh the solids content of the supernatant to calculate its dispersion rate. See Table 3. The total solid content was 2g, and the particle masses in the supernatant were S1 (0.40g), S2 (0.30g), S3 (0.26g), S4 (0.60g), S5 (0.36g), S6 (0.80g), S7 (0.70g), and S8 (0.56g), respectively. Their dispersion rates were S1 (20.0%), S2 (15.0%), S3 (13.0%), S4 (30.0%), S5 (18.0%), S6 (40.0%), S7 (35.0%), and S8 (28.0%), respectively.

[0037] As can be seen from the overall trend, experimental groups S2 and S3 still performed superiorly, with centrifugal suspension rates of 15.0% and 13.0%, respectively, which were far lower than those of the traditional KCl inhibitor (S6 / S7 groups, with dispersion rates of 40.0% and 35.0%, respectively) and the unmodified chitosan group (S8, 28.0%). This indicates that the chitosan-quaternary ammonium salt composite inhibition system constructed in this invention can effectively stabilize the shale particle interface, inhibit particle exfoliation, and reduce the degree of solid phase dispersion. Group S4, due to insufficient modification concentration, still had a suspension rate of 30.0%, indicating poor anti-dispersion performance. While group S5 had a higher addition amount, its dispersion rate was slightly higher than that of groups S2 / S3 because it might form excessive cross-links or increase solution viscosity, leading to decreased diffusion and adsorption uniformity. This suggests that optimizing the ratio is more crucial than simply increasing the dosage.

[0038] The results in summary confirm that the composite cationic modified chitosan has significant advantages in dispersion inhibition, especially in maintaining interfacial stability at high temperatures, thus providing effective protection for wellbore integrity.

[0039] The composite inhibitor proposed in this invention exhibits superior anti-dispersion performance, with a dispersion rate of less than 20%, significantly better than the aforementioned control groups. Its excellent performance is attributed to the strong adsorption and surface activity of the cationic modified chitosan in the composite system, as well as the synergistic effect of glycine molecules on shale pores, enabling it to stabilize the clay structure, inhibit particle stripping, and reduce the content of suspended solid particles in the drilling fluid under high-temperature circulating conditions.

[0040] In summary, through systematic testing and comparative analysis of three key indicators—free expansion rate, thermal expansion rate, and dispersion performance—the excellent inhibitory performance of the chitosan-quaternary ammonium salt composite shale inhibitor prepared in this invention in water-based drilling fluid systems has been verified.

[0041] In the free expansion experiment, the typical formulations (such as S2 and S3 groups) can effectively control the expansion rate of bentonite at 42.5% and 40.0%, which is significantly lower than that of the 5% and 10% KCl control groups (expansion rates of 95.0% and 87.5%, respectively) and the unmodified chitosan group (72.5%), demonstrating good initial hydration inhibition ability.

Claims

1. A chitosan-quaternary ammonium salt modified composite shale inhibitor and its preparation method, characterized in that: (1) Weigh 15-25 parts by weight of chitosan powder (degree of deacetylation 80%-90%, molecular weight 100,000-200,000), slowly add it to 1,000 parts of 1% glacial acetic acid aqueous solution, and stir continuously at room temperature (25°C) for 1.2-2.5 hours to form a uniform solution. (2) Under stirring, slowly add 2 to 4 parts of dimethyl diallyl ammonium chloride (DMDAAC) to the above chitosan solution. During the addition process, keep the system temperature between 65 and 75°C. After the addition is completed, continue stirring for 25 to 35 minutes to ensure that the monomer is evenly dispersed. (3) Dissolve 0.1 to 1 part ammonium persulfate (APS) as a free radical initiator in 10 parts distilled water, and slowly add it dropwise to the reaction system. Maintain the reaction temperature at 65 to 75°C for 3.5 to 4.5 hours to carry out the graft copolymerization reaction; (4) After the reaction is completed, the mixture is allowed to cool naturally to room temperature, filtered to remove unreacted impurities, and dried to obtain a light yellow modified chitosan inhibitor solid powder. (5) Add 10-20 parts of the obtained inhibitor powder to 1000 parts of deionized water, and stir magnetically for 25-30 minutes at room temperature until completely dissolved to form a uniform inhibitory solution. Then add 1.5-2.5 parts of glycine as a synergistic agent and continue stirring until uniform to finally obtain a composite shale inhibitory solution.

2. The preparation method according to claim 1, wherein the weight ratio of modified chitosan to 1% glacial acetic acid in step (1) is (10-30):(800-1100), preferably (15-25):(950-1050).

3. The preparation method according to claim 1, wherein the weight ratio of chitosan mixed solution to dimethyl diallyl ammonium chloride (DMDAAC) in step (2) is (900~1100):(1.5~4.5), preferably (950~1000):(2.5~3.5).

4. The preparation method according to claim 1, wherein the weight ratio of chitosan mixed solution to ammonium sulfate in step (3) is (950~1050):(0.1~1), preferably (980~1020):(0.4~0.6).

5. The preparation method according to claim 1, wherein the weight ratio of inhibitor:water:glycine in step (5) is (10~20):(950~1050):(1.5~2.5), preferably (14~16):(980~1020):

2.

6. The preparation method according to claim 1, wherein the stirring time in step (1) is 1.5 to 2.5 hours, preferably 2 hours, and the stirring rate is 200 to 400 rpm, preferably 300 rpm.

7. The preparation method according to claim 1, wherein the graft copolymerization time in step (3) is 4.5 to 5.5 hours, preferably 5 hours; wherein the temperature in steps (2) and (3) is 65 to 75°C, preferably 70°C.

8. The preparation method according to claim 1, wherein in step (4), the drying temperature is 40~60℃, preferably 50℃; and the drying time is 12~24 hours, preferably 18 hours.

9. The preparation method according to claim 1, wherein the chitosan is preferably derived from the deacetylated product of natural shrimp or crab shells, with a degree of deacetylation of 80-90% and a molecular weight controlled at 5 × 10⁻⁶. 4 ~2×10 5 between.

10. The preparation method according to claim 1, wherein the cationic monomer is preferably dimethyl diallyl ammonium chloride (DMDAAC), which contains two allyl double bonds and a quaternary ammonium cationic group in its molecular structure.

Citation Information

Cited By

  • Polymer coating inhibitor for strong-inhibition drilling fluid and preparation method of polymer coating inhibitor

    CN122255956A